Experimental and Numerical Analysis of Torque Properties of Rotary Elastomer Particle Damper considering the Effect of Gap and No Gap between Rotor and Body of the Damper - Allah Rakhio; Yasushi Ido; Yuhiro Iwamoto; Atsushi Toyouchi (Shock and Vibration)
Particle dampers are devices used to control the vibration of mechanical systems. In this research, prototypes of rotary elastomer particle dampers are experimentally tested considering gap and no gap between shaft and cylinder. There is a gap between the rotor and cylinder in the gap model; particles can move from one chamber to another. There is no space for the particles to move from one chamber to another in the no-gap model. Elastomer particles are soft, and they have different behavior from hard (metallic) particles. Experiments on rotary elastomer particle dampers considering the gap between rotor and cylinder helped investigate the effects of the change in packing fraction, rotational speed, size of elastomers, and the gap between the rotor and the damper body. A numerical simulation approach based on the discrete element analysis method is used to perform a quantitative and qualitative analysis of the rotary elastomer particle damper. The simulation results are in great agreement with the experiment results. It is observed that packing fraction, rotational speed, size of elastomer particles, and the gap between rotor and cylinder play a vital role in producing higher damper torque.